Notaire d’aujourd’hui, notaire d’autrefois - M., R. (Assurances)

(untitled) (HEC Montréal, 1984)
The notary of today possesses the same legal education as a lawyer, except that after obtaining his diploma, the notary is offered specialized courses. A wide variety of refresher courses are currently being offered to notaries and are designed to keep them abreast of their profession. It is interesting to compare the present-day notary to his counterpart of yesterday, namely, the notary of the late eighteenth or early nineteenth century who obtained the right to exercise his profession by forwarding a request to the Governor General seconded by three eminent citizens.